High Full‐Electrode Basis Capacity Template‐Free 3D Nanocomposite Secondary Battery Anodes. Issue 47 (19th October 2015) - Liu, Jinyun; Wang, Junjie; Kim, Jinwoo; Ning, Hailong; Pan, Zeng; Kelly, Sean J.; Epstein, Eric S.; Huang, Xingjiu; Liu, Jinhuai; Braun, Paul V.
Abstract : A high full‐electrode basis capacity secondary battery anode consisting of a template‐free 3D nanostructured Fe3 O4 /C composite is presented. On a full electrode basis, the nanocomposite exhibits attractive electrochemical performance including a volumetric capacity of 1064 mAh cm −3, which significantly exceeds both the practical (≈300 mAh cm −3 ) and theoretical (837 mAh cm −3 ) capacity of a commercial graphite‐based anode.